Benchmarking of single‐virus genomics: a new tool for uncovering the virosphere. (17th January 2021) - Garcia‐Heredia, Inmaculada; Bhattacharjee, Ananda S.; Fornas, Oscar; Gomez, Monica L.; Martínez, Joaquín M.; Martinez‐Garcia, Manuel
Summary: Metagenomics and single‐cell genomics have enabled the discovery of relevant uncultured microbes. Recently, single‐virus genomics (SVG), although still in an incipient stage, has opened new avenues in viral ecology by allowing the sequencing of one single virus at a time. The investigation of methodological alternatives and optimization of existing procedures for SVG is paramount to deliver high‐quality genomic data. We report a sequencing dataset of viral single‐amplified genomes (vSAGs) from cultured and uncultured viruses obtained by applying different conditions in each SVG step, from viral preservation and novel whole‐genome amplification (WGA) to sequencing platforms and genome assembly. Sequencing data showed that cryopreservation and mild fixation were compatible with WGA, although fresh samples delivered better genome quality data. The novel TruPrime WGA, based on primase‐polymerase features, and WGA‐X employing a thermostable phi29 polymerase, were proven to be with sufficient sensitivity in SVG. The Oxford Nanopore (ON) sequencing platform did not provide a significant improvement of vSAG assembly compared to Illumina alone. Finally, the SPAdes assembler performed the best. Overall, our results represent a valuable genomic dataset that will help to standardized and advance new tools in viral ecology.